Retraction notice to "Long-Term Trends (1986-2003)in the Use of Coronary Reperfusion Strategies in Patients Hospitalized With Acute Myocardial Infarction in Central Massachusetts" [Int. J Cardiol. 131 (2008) (83-89)]. (15th May 2017) - Goldberg, Robert J.; Spencer, Frederick A.; Okolo, Joseph; Lessard, Darleen; Yarzebski, Jorge; Gore, Joel M.
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy ). This article has been retracted at the request of the Editor-in-Chief and Author. This article is a duplicate of a paper that has already been published in the Journal of Thrombosis and Thrombolysis, 23 (2007) 163-71.http://dx.doi.org/10.1007/s11239-006-9029-0 . One of the conditions of submission of a paper for publication is that authors declare explicitly that the paper is not under consideration for publication elsewhere. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.